2017
DOI: 10.1101/106443
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visibility graphs for fMRI data: multiplex temporal graphs and their modulations across resting state networks

Abstract: Visibility algorithms are a family of methods that map time series into graphs, such that the tools of graph 1 theory and network science can be used for the characterization of time series. This approach has proved a 2 convenient tool and visibility graphs have found applications across several disciplines. Recently, an approach has 3 been proposed to extend this framework to multivariate time series, allowing a novel way to describe collective 4 dynamics. Here we test their application to fMRI time series, f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 67 publications
(154 reference statements)
0
15
0
Order By: Relevance
“…Research on this methodology has been primarily theoretical, elaborating on mathematical methods [28][29][30][31] to extract rigorous results on the properties of these graphs when associated to canonical models of complex dynamics, including stochastic processes with and without correlations or chaotic processes [32][33][34][35] . In practice, this method can be used as a feature extraction procedure for constructing feature vectors for statistical learning purposes and has been widely applied across the disciplines (see, for instance, [36][37][38][39][40] for just a few examples).…”
Section: Horizontal Visibility Graph Motifsmentioning
confidence: 99%
“…Research on this methodology has been primarily theoretical, elaborating on mathematical methods [28][29][30][31] to extract rigorous results on the properties of these graphs when associated to canonical models of complex dynamics, including stochastic processes with and without correlations or chaotic processes [32][33][34][35] . In practice, this method can be used as a feature extraction procedure for constructing feature vectors for statistical learning purposes and has been widely applied across the disciplines (see, for instance, [36][37][38][39][40] for just a few examples).…”
Section: Horizontal Visibility Graph Motifsmentioning
confidence: 99%
“…Building upon the mapping of multivariate time series into a multilayer graph proposed in [ 34 ], Sannino and co-authors described an approach to capture modulations across resting-state networks [ 35 ]. Sannino et al observed that the networks within the multiplex layers have a modular structure which is an indication of different temporal regimes.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Partitioning the visibility graph based on these modules provides a natural decomposition of the time series into time intervals. The approach presented in [ 35 ] is to capture the similarity between neural events using Sörensen similarity index between each pair of modules in the two time series. One difference from our approach is that we did not use a visibility criterion; another difference is that the approach in [ 35 ] is based on decomposing time series into time intervals.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations